(untitled) (Canadian Eye Care Today, 2024)
Patients present to the ophthalmologist with various corneal pathologies, and it is imperative to differentiate the benign from the malignant at the slit lamp to provide them proper guidance and treatment. These conditions tend to play a more significant role in the pre-operative cataract evaluation as they typically affect post-operative visual rehabilitation. In this review, we aim to examine the differentiating factors of the many lumps and bumps that affect the cornea and the available ways for surgeons to treat them in Canada.